1996
DOI: 10.1590/s0102-311x1996000400004
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos eco-epidemiológicos da leishmaniose tegumentar americana no Município de Campinas

Abstract: The authors describe an outbreak of American cutaneous leishmaniasis from February 1993 to September 1994 in the districts of Sousas and Joaquim Egídio, Campinas, São Paulo State. Out of a total of 25 cases, seven occurred in the countryside, nine in the periurban area, and nine in the urban area. The authors observed a shift in the occurrence of leishmaniasis cases from rural to urban areas. Cases in males predominated over females (60%/40%). Some 44% of the cases occurred in individuals ranging from 11 to 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 4 publications
3
10
1
2
Order By: Relevance
“…This result was lower to that observed by Gomes et al (1992), in the Vale do Ribeira, São Paulo, where 10.2% (27/273) were seropositive, by Silveira et al (1996a) Among the seropositive there were women, children and people who reported that they performed only housework. These findings are in agreement with observations from the literature where the infection may be occurring in domiciliary and peridomiciliary area (CUNHA; LIMA; POMPEU, 2006;CORTE et al 1996;FALQUETO et al, 1986FALQUETO et al, , 1991GOMES et al, 1992;OLIVEIRA NETO et al, 1988).…”
Section: Discussionsupporting
confidence: 92%
“…This result was lower to that observed by Gomes et al (1992), in the Vale do Ribeira, São Paulo, where 10.2% (27/273) were seropositive, by Silveira et al (1996a) Among the seropositive there were women, children and people who reported that they performed only housework. These findings are in agreement with observations from the literature where the infection may be occurring in domiciliary and peridomiciliary area (CUNHA; LIMA; POMPEU, 2006;CORTE et al 1996;FALQUETO et al, 1986FALQUETO et al, , 1991GOMES et al, 1992;OLIVEIRA NETO et al, 1988).…”
Section: Discussionsupporting
confidence: 92%
“…Corte e cols descreveram o surto da doença em parte da região Leste (Sousas e Joaquim Egídeo) associando o surgimento de casos à expansão urbana com desmatamento e preservação de pequenas áreas circunscritas de matas residuais, ciliares e resultantes de reflorestamento 5 . Após a consolidação imobiliária na região notificou-se um silêncio epidemiológico embora as matas continuem preservadas.…”
Section: Figuraunclassified
“…Previous studies show a correlation between cases of AVL and the distance between forest and residences in which the risk of infection by L. chagasi was higher in dogs living in areas of dense vegetation compared to dogs living at a distance of 100m or farther from forest areas 10,11 . Although autochthonous canine cases of AVL have been identifi ed in this region only since 2009, an outbreak of human American tegumentary leishmaniasis (ATL) was documented previously in this same area between 1993 and 1994 12 . Cases of ATL were associated with the presence of riparian forest or small fragments of wooded areas.…”
Section: Entomological Researchmentioning
confidence: 99%
“…Cases of ATL were associated with the presence of riparian forest or small fragments of wooded areas. The great majority of cases suggested that the residence itself was the probable site of infection, and these residences were always situated close to or inside the forest 12,13 .…”
Section: Entomological Researchmentioning
confidence: 99%
See 1 more Smart Citation